Nonlinear relationship between lumbar bone mineral density and high-density lipoprotein cholesterol in patients with type 2 diabetes - He, Yu-Hua; Gu, Shi-Li; Chen, Yang-Yang; Xue, Ming-Mei; Liu, Su-Juan; Guo, Fang-Fang; Liang, Chang-Hua (Frontiers in Endocrinology, 2025)
BackgroundHigh-density lipoprotein cholesterol (HDL-C) plays a significant role in regulating bone mineral density (BMD), with this relationship being influenced by insulin resistance. Although previous studies have investigated the relationship between HDL-C and BMD in patients with type 2 diabetes mellitus (T2DM), the impact of fasting blood glucose (FBG) on this association remains unclear. This study analyzes health screening data from T2DM patients to investigate the relationship between lumbar BMD and serum HDL-C, while also examining how FBG mediates this association.MethodsThis retrospective analysis involved T2DM patients who underwent lumbar BMD screening at our hospital from January 2019 to December 2023. Lumbar BMD was measured via quantitative computed tomography. This study mainly aimed to explore the relationship between lumbar BMD and serum HDL-C in T2DM patients and assess the mediating role of FBG. Statistical analyses employed comprehensive methods: univariate analysis to examine initial variable relationships, generalized additive models for non-linear curve fitting, segmented regression for threshold effects, stratified subgroup analysis to explore potential effect modifications, and mediation analysis to explore potential indirect effect mechanisms.ResultsThis work revealed that after controlling confounding factors, an independent nonlinear correlation was observed between lumbar BMD and serum HDL-C in T2DM patients. When HDL-C > 1.35 mmol/L, T2DM patients’ lumbar BMD shows a significant positive correlation [β=3.32, 95% confidence interval (CI): 1.43, 4.21, P=0.010)]. Subgroup analysis results indicated the consistent relationship between lumbar BMD and serum HDL-C in T2DM patients across gender (male/female), age (≤40 years/>40, ≤60 years/>60 years), and body mass index (<24 kg/m2/≥24, <28 kg/m2/≥28 kg/m2) subgroups (all P interaction > 0.05). Analysis of the mediation effect revealed that FBG mediated 5.38% of the association, with an indirect effect of -0.142 (95% CI: -0.327, -0.026, P=0.014).ConclusionThe independent nonlinear, J-shaped association between lumbar BMD and serum HDL-C in T2DM patients was detected in this study, with FBG negatively mediating this relationship. These findings prove the effect of lipid metabolism and glucose dysregulation on bone health and contribute to the development of osteoporosis prevention and treatment strategies for T2DM patients.